Implementation of Digital Learning Media in Increasing Elementary School Students' Interest in Learning: A Literature Review - Samsidar Samsidar (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the implementation of digital learning media in increasing elementary school students' learning interest through a literature review. The method used is a qualitative approach with content analysis techniques on various relevant scientific sources, including journal articles, proceedings, and books published in the last five years (2019–2024). The results of the study indicate that the use of digital media, such as interactive videos, animations, educational games, and learning applications, contributes positively to increasing learning interest through attractive, interactive, and contextual presentations. Student learning interest increases when digital media is combined with appropriate pedagogical strategies, such as constructivist-based learning, blended learning, and simple gamification. However, the success of digital media implementation is also influenced by supporting factors such as teacher competence, technological infrastructure, and media design that is appropriate to student characteristics. This study emphasizes the need for ongoing teacher training, media development based on instructional design principles, and a comprehensive evaluation of the impact of digital media on learning interest. With appropriate implementation, digital learning media has the potential to create more meaningful learning experiences and foster positive attitudes towards long-term learning.